Deliberative Mini-Publics: Core Design Features - David M. Farrell; Nicole Curato; John S. Dryzek; Brigitte Geißel; Kimmo Grönlund; Sofie Marien; Simon Niemeyer; Jean-Benoit Pilet; Alan Renwick; Jonathan Rose; Maija Setälä; Jane Suiter (University of Canberra/Centre for Deliberative Democracy & Global Governance, 2022)
This working paper identifies core design features of a deliberative mini-public (DMP). It aims to provide clarity on what distinguishes a DMP from other forms of citizen engagement and participation by characterising its normative foundations and setting out its key features under a series of discrete headings that can be used as a resource by anyone designing, implementing, or studying DMPs.